The Use of Quizlet to Improve The Students’ Vocabulary Mastery of The 10th Grade of UPT SMA Negeri 2 Parepare - Sakti, Nur Sri (La Parole : Journal of Language Teaching and Pedagogy, 2022)
The objectives of this research are to find out whether or not the use of Quizlet can improve the students’ vocabulary mastery in the 10th grade of SMA Negeri 2 Parepare and to see the students’ response to the use of Quizlet. The mixed method was used in this research. The researcher collected both qualitative and quantitative data. The quantitative was taken through pretest and post-test while the qualitative data was taken through interviews. The result of quantitative data showed that there were only 9 students who reached the minimum criteria of KKM score before the implementation of Quizlet, with an average score of 56.46, while the percentage was 37.5% in the pre-test. After the treatment and the implementation, there were 12 students who reached the minimum criteria of KKM score, with an average score of 73.63, while the percentage was 50%. It shows that the use of Quizlet during the learning process can improve students' vocabulary mastery. Meanwhile, qualitative data revealed that the students' responses were positive; they enjoyed and felt interested in learning vocabulary using Quizlet because it is simple to use, has some interesting features, and helps them memorize the new words.